2008
DOI: 10.1055/s-2008-1081498
|View full text |Cite
|
Sign up to set email alerts
|

Foot Temperature in Type 2 Diabetic Patients with or without Peripheral Neuropathy

Abstract: Foot temperature is significantly higher in type 2 diabetic patients with neuropathy as compared to those without neuropathy. In patients with neuropathy, a significant positive correlation is observed between foot temperature and clinical severity of neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
1
29
0
2
Order By: Relevance
“…Plantar temperatures in diabetic neuropathic patients have been reported to be higher compared to non-neuropathic patients and/or healthy individuals (Bagavathiappan et al, 2010;Papanas et al, 2009;Sun et al, 2006Sun et al, , 2008Yavuz et al, 2014). This was attributed to the presence of inflammation within the tissue, a common outcome in such patients.…”
Section: Discussionmentioning
confidence: 93%
“…Plantar temperatures in diabetic neuropathic patients have been reported to be higher compared to non-neuropathic patients and/or healthy individuals (Bagavathiappan et al, 2010;Papanas et al, 2009;Sun et al, 2006Sun et al, , 2008Yavuz et al, 2014). This was attributed to the presence of inflammation within the tissue, a common outcome in such patients.…”
Section: Discussionmentioning
confidence: 93%
“…Both tests have already been reported to be reproducible 10,13 and to have value for patient self-examination. 8,9,14 It was shown that patients with sudomotor dysfunction exhibited significantly higher foot temperature than those without sudomotor dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…10,11 Peripheral arterial disease was defined as ankle-brachial index <0.9 in at least one limb, as measured by the authors using a handheld 8 MHz Doppler device (MiniDop handheld Doppler, Hadeco, Inc., Japan) and a sphygmomanometer. 15 Other potential causes of peripheral neuropathy and peripheral nerve lesions were excluded on the basis of patients' medical history.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12]. Also, in conditions that lead to higher or lower foot temperatures, such as arteriovenous shunts and atherosclerosis, the tempera-ture change is often evenly distributed between the feet [13]. Consequently, there seems to be a rationale for determining foot temperatures in diabetic patients.…”
Section: Foot Ulcers and Temperature Monitoringmentioning
confidence: 99%